Mexico : 2020 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2020)
Covid-19 has exacted a tragic human, social, and economic toll on Mexico. Over 85,000 lives were lost; unofficial estimates are notably higher. Of 12 million workers that lost their jobs, most of whom came from the informal sector with a limited safety net, over 4 million remain out of the workforce. The working poverty rate jumped to 48 percent. After a historic drop in output, there has been a trade-led bounce in manufacturing. But domestic demand is weak, as is services activity that employs most of the workforce. Staff projects the economy to shrink by 9 percent this year, followed by a gradual recovery. It could take years for employment and incomes to return to pre-crisis levels, compounding the long-standing challenge of achieving strong and inclusive growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet